Web Performance Analytics: WebQEM In Academic Portal - Reynaldo Joshua Salaki; Kenneth Yosua Palilingan; Salvius Paulus Lengkong; Yuri Vanli Akay; Heilbert Armando Mapaly; Henry Valentino Kainde (Jurnal Teknik Elektro dan Komputer, 2021)
Academic portal is a website service by the university in providing information and management of academic data. The characteristics of an academic information system are academic content, periodic accessibility, level of user authority, precision and accuracy. Some of these characteristics are then mapped into quality factors adopted from various models, such as ISO-9126, Website quality Model, and academic website quality model. The results of the mapping obtained five quality factors proposed to carry out quality measurements, namely usability, functionality, content, efficiency and reliability. These five quality factors serve as measurement objectives. The WebQEM method is used to obtain internal metrics to produce objective and quantitative measurements. Metrics produced from the GQM method are validated using empirical validation. Internal product metrics are applied in a case study of a university-based academic information system for Universities in North Sulawesi. The focus of research conducted by researchers is to measure the quality factor Efficiency at Sam Ratulangi University and Manado State University. The results obtained for YSlow and PageSpeed, at Sam Ratulangi University and Manado State University found the lowest difference in the Pagespeed result